Armouring solutions against high-velocity impact using 2D laminates and 3D warp interlock composites. (April 2014) - Provost, Benjamin; Boussu, François; Coutellier, Daniel; Vallee, Daniel; Rondot, Fabien; Nussbaum, Julien
Since the emergence of the first armoured vehicles on battlefields, armour shield was mainly centred on conventional metallic materials, widespread solutions nowadays. For a long time, weight reduction in armoured protection, which represents the largest part of the vehicle's overall weight, has been the key parameter for vehicle manufacturers looking forward to optimizing fuel consumption, thus increasing the payload and offering increased manoeuvrability to vehicles. The solution generally developed is a combination between those metallic plates and materials lighter than the current steel armour. In this context, the hybridization of some well-known ballistic alloys with textile composite materials appears to be a high-potential solution for armour-plated protection. Indeed, used as a backing, textile composite materials present some worthwhile properties such as having a very low density compared with steel and good behaviour in terms of ballistic efficiency. The use of a textile composite backing allows a reduction in the thickness of the metal plate by a few millimetres, which has a huge impact on the total protection weight. The difficulty of this hybridization is, of course, to reduce the total mass of the protection solution as cautiously as possible while ensuring the safety of the vehicle. The textile composite backing is also efficient in containing the pieces of shrapnel, which might break loose from the metal plate during impact. However, observations from today's military theatres of operation reveal that the spectrum of armoured vehicle threats has changed over the last decade with the development of new non-conventional threats commonly referred to as 'improvised explosive devices'. Those devices generate high-velocity projectiles (accelerated up to a few hundred or thousand metres per second), which are able to perforate most existing armour plating. Thus, performances of today's armoured solutions are required to be upgraded, in order to provide a better protection level. This improved protection level against new threats can be achieved by developing a composite backing more efficient to stop these projectiles. This study proposes to test and compare the behaviour and efficiency of three different textile composite backings used as up-armouring solutions. Two of those textile backings are innovative composite solutions developed in our textile laboratory, and the third one is a benchmark composite generally used as armouring protection. This study deals with the overall protection, and impact tests are performed on real armour configuration with the metal plate on the front face. Nevertheless, only the impact behaviour of textile composite backings has been investigated in this study. The parameters of the metal plate such as the nature of the alloy and its thickness were defined by our vehicles' manufacturing partner and cannot therefore be communicated. They remain constant in the three configurations tested, allowing a clear comparison.